STUDI PERFORMANSI ECONOMIZER JENIS ALIRAN SILANG UNTUK PROSES DEGREASING DI PT. X PLANT KARAWANG - Komarudin, Komarudin; Rahmaputra, Reza (Bina Teknika, 2018)
Economizer is Heat Exchanger with Crossflow type that have function as reheater the  water to degreasing process. System of Economizer had operated continuously for 7 years. So from this condition Effectiveness and Temperature possibility Can’t achieve the Requirement. Degreasing Process is a part of Painting process in Vehicle manufacturing that have function to degrease the oil, dust and etc.  A decrease in the effectiveness of this, we need recalculation and compare  with design condition to get better effectiveness. Analysis will be refer to fluid flow, overall heat transfer coefficient (U), and Efffectiveness of Economizer it self. Based on result of Calculation and Experiment, the flow of fluid is turbulent flow with Reynold number 12002.14 (Max Condition). Overall heat transfer coefficient (U) is 16.18 W/mK, while the design condition is 48 W/m.K also for Effectiveness is 32.16% and the design condition is 50%. This calculation Proved decreasing of that the performance of economizer. It is caused by scaling of the inner pipe with ratio 2.26%. Scaling will be reduce thermal conductivity of the pipe and also gradient of Temperature.